Reproductive variables and Correlation between Irrational Parenthood Cognition and Destructive Behaviors of Marital Relationship in Infertile Women - Safaei Nezhad A; Vakili MM; Ebrahimi L; Kharaghani R (Zanjan University of Medical Sciences and Health Services, 2017)
Background: Reproductive variables may play an important role on the correlation between irrational parenthood cognition (IPC) and destructive behaviors of infertile couple. Objectives: The aim of this study was to determine the correlation between IPC and destructive behaviors by reproductive variables in primary infertile women. Methods: The study was descriptive-analytic. 183 cases of primary infertile women living in Zanjan-Iran and attended to the Infertility Clinic in Ayatollah Mousavi Hospital were investigated from 2015 to the end of 2016. The instrument included a three-part questionnaire of individual and reproductive information, IPC, and the destructive behaviors of marital relationship based on Glaser's choice theory. Data were analyzed by SPSS software using descriptive and Pearson correlation test (P<0.05). Results: There was a significant direct correlation between IPC and destructive behaviors of marital relationship in infertile women (r=0.47, p<0.001). Based on reproductive variables, the highest correlation was observed in the subgroups of less than 10 years elapsed from the diagnosis of infertility, less than 10 years from the onset of infertility treatment, and the expectation of pregnancy under 10 years, a history of twice unsuccessful in vitro fertilization, a tendency to pregnancy due to the pressure of the others and the cause of the unknown infertility (P<0.05). Correlation between IPC and all components of destructive behaviors was significant (p<0.001). Conclusion: Identifying infertile women with high IPC and destructive behaviors is important to educate regarding life skills and provide counseling services.